Diagnosis and Management of Fungal Periprosthetic Joint Infections. Issue 18 (15th September 2019) - Nace, James; Siddiqi, Ahmed; Talmo, Carl T.; Chen, Antonia F.
Abstract : Fungal periprosthetic joint infection (PJI) is a devastating complication because it can be difficult to diagnose, manage, and eradicate. Fungal PJI treatment requires a systematic approach. Increased awareness is essential when patients with painful arthroplasties present with immunosuppression, significant comorbidities, multiple surgeries, and history of drug use. Every suspected fungal PJI should be promptly diagnosed using readily available serum and synovial fluid markers. Surgical management involves débridement, antibiotics, and implant retention, one-stage exchange arthroplasty, prosthetic articulating spacers, and two-stage exchange arthroplasty. Because mycotic infections develop robust biofilms, the utility of débridement, antibiotics, and implant retention and one-stage revisions seem limited. A thorough irrigation and débridement is essential to decrease infection burden. Adjunctive local and systemic antifungal therapy is critical, although the agent choice and duration should be tailored appropriately. Future high-quality studies are needed to develop standardized guidelines for the management of fungal PJI.